Flood and Flash Flood Geo-Hazards in Malaysia - Buslima, F. S.; Omar, R. C.; Jamaluddin, Tajul Anuar; Taha, Hairin (International Journal of Engineering and Technology, 2018)
Floods are natural phenomena of geo-hazards that usually happened when experiencing prolonged heavy rainfalls. Floods in Malaysia can be categorized into monsoon floods and flash floods. Monsoon floods is caused of Northeast Monsoon season commences in early November and ends in March that brings heavy rainfall, particularly to the east coast states of Peninsular Malaysia and western Sarawak. Flash floods usually occur in areas with rapid development by a rapid rise in water level, high velocity, and large amounts of debris. Flooding that occurred in December 2014 can be classified as worst floods that affected several states in Peninsular Malaysia, and the worst affected is Kelantan state. This disaster was recorded more than 200,000 people were affected with 21 people were killed and gives a massive impact on people, properties, agriculture, livestock, and infrastructure facilities. Following the worst floods that hit Malaysia in 2014, the opinions and views from various parties such as subject matter experts was needed to produce mitigations and prevents of the flood disaster at once to minimize vulnerability to hazard.